-5.9=(h/5)+12.2

Simple and best practice solution for -5.9=(h/5)+12.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5.9=(h/5)+12.2 equation:



-5.9=(h/5)+12.2
We move all terms to the left:
-5.9-((h/5)+12.2)=0
We add all the numbers together, and all the variables
-((+h/5)+12.2)-5.9=0
We multiply all the terms by the denominator
-((+h-(5.9)*5)+12.2)=0
We calculate terms in parentheses: -((+h-(5.9)*5)+12.2), so:
(+h-(5.9)*5)+12.2
We calculate terms in parentheses: +(+h-(5.9)*5), so:
+h-(5.9)*5
determiningTheFunctionDomain h-(5.9)*5
We add all the numbers together, and all the variables
h-29.5
Back to the equation:
+(h-29.5)
We get rid of parentheses
h-29.5+12.2
We add all the numbers together, and all the variables
h-17.3
Back to the equation:
-(h-17.3)
We get rid of parentheses
-h+17.3=0
We add all the numbers together, and all the variables
-1h+17.3=0
We move all terms containing h to the left, all other terms to the right
-h=-17.3
h=-17.3/-1
h=17+0.3/1

See similar equations:

| 11-7x2=-157 | | -9+b=7+4-4b | | 3x+6x/2=72 | | 5x2+41x+40=-2 | | 12(8c-4)=7c-7 | | -3c/10-31=83 | | 5q-7=2q+8 | | 3(c+4)-6c=2(4-2c) | | -2+6c=-10+5c | | 77=1x+7x+5 | | -15/4=5u | | 7.5=5x | | 17.5-10=5x | | -4y=-7y+6 | | 17.5=5x+10 | | 4x=(1+5-8) | | 2+2a=54 | | -6+3x=-39 | | 3y2-2×-6y=0 | | 2(4x-1)=26X= | | 3r-5+3=16 | | (1/2x)+(1/6)=3/4 | | 21=−2t+3 | | 5m+6m=−3 | | -5-2x-7=-4 | | -(3-2n)+7=3(n+3) | | 16.4+2x=7.5+7.5x | | 8+11x=140 | | -(1y+8)-5=4(y+2)-6y | | x-42=76 | | |9-3n|=3 | | x-40=-63 |

Equations solver categories